National Health Service : deputation to Minister of Health on 17 June 1946 (report) - Bevan, Aneurin, 1897-1960
1946-06-25 1946 1940s 9 pages -2- as possible, and financial circumstances should not be allowed to limit recruitment for the services. Social circumstances and other factors had prevented many men and women from entering the medical profession. Conditions of Employment and Remuneration The remuneration and general conditions of life of a medical practitioner in the new service should be no less favourable than those of other professions. It was hoped that the Spens Committee Report would help in this direction. Buying and Selling of Practices The T.U.C. endorsed the Minister's decision on this point. In the drafting of the regulations, the possibility of provision being made for a doctor to be paid wholly on a salaried basis if he so desired, should be considered. Health Centres Those centres instituted it was hoped would provide a first class service and facilities for educational health work. Hospital System The General Council appreciated the Government's decision to incorporate the voluntary hospitals in one unified hospital system and hoped that they would not experience too much difficulty in that respect. Administration The T.U.C. felt that the medical membership of the Central Health Services Council was too large. They were not anti-medical and did not want to minimise the importance of the profession in this matter but at the same time they wanted to be equally fair all round. There should be more adequate representation of nurses, midwives, etc. They wished to suggest that the period of appointment to the Council should be for a reasonable length of time, say 5 years, with power to renew such appointments. Standing Advisory Committees They would be glad to have clarification as to the Standing Advisory Committees which it was proposed to set up. Regional Hospital Boards These Boards presumably had power to fix remuneration and conditions of service. They would like to know whether that applied to all types of hospital employees. Proportion of Representation on the Boards It would help considerably if the Minister could give an indication as to his intentions in this regard. Boards of Governors The General Council felt that the scale was heavily weighted in favour of the representation of the medical profession on these Boards. They felt that local authorities, nurses and other health workers should also have adequate representation. The success of a hospital did not only depend upon the medical 292/847/4/113